Remote Access to Expensive SDRAM Test Equipment: Qimonda Opens the Shop-floor to Test Course Students - Ana C. Leão (2007)
Remote labs are increasingly used in a variety of blended-learning scenarios, with the objective of complementing the work done in real labs. In such cases, the workbenches present in the real labs comprise a set of instruments that may be used over the internet. The lab work to be done by the students may be carried out from any location within or outside the campus, enabling them to carry out their assignments from home or from any other place, at a time of their choice. However, remote experimentation is not necessarily related to students accessing academic labs. Small and medium-size companies may be interested in specialised equipment available in university research labs (e.g. an electron microscope). Alternatively, student skills in various areas may be improved if they are able to work with equipment available in factories or other industry installations. This paper describes a collaboration initiative between the Qimonda SDRAM factory at Vila do Conde, in the vicinity of Porto, and the Faculty of Engineering of the University of Porto (FEUP), whereby an expensive test station used by Qimonda SDRAM factories is remotely accessible to test course students in higher-education institutions.